Strategi Penguatan UMKM Melalui Model Pentahelix Di Kabupaten Purworejo - Tri Wahyu Lestari; Uswatun Chasanah; Muhammad Mathori (Jurnal Syntax Admiration, 2023)
This study aims to analyze MSME exporters in Purworejo Regency which operate in the sugar cluster, specifically the Srikandi Women's Cooperative and the Karmatera Cooperative. The data from the analysis is then used as reference material to formulate strategic steps in the form of designing a model to increase the competitiveness of MSMEs through pentahelix collaboration. Synergy between interested parties provides export space for MSMEs to be competitive in surviving and increasing exports of MSME products. This research was conducted using a qualitative approach to formulate a model design for increasing the competitiveness of MSMEs. Data was obtained from interviews, field notes and documentation, by organizing the data into categories, describing it into units, synthesizing it, arranging it into patterns, choosing what is important and what will be studied, and making conclusions. The research results show that collaboration between stakeholders is expected to be a model for increasing the competitiveness of MSMEs in international markets (exports).